Seasonarity of turbulent energy dissipation rates over Syowa Station, Antarctic - Kohma, Masashi; Sato, Kaoru (2022)
The 13th Symposium on Polar Science/Interdisciplinary sessions [IW] Whole atmosphere, Fri. 18 Nov. conference object